The Role of Parents in Supporting Early Childhood Learning Activities: Peran Orangtua dalam Mendampingi Kegiatan Belajar Anak Usia Dini - Muhimatun Hasanah; Sefriyanti; Anita Oktaviana (Universitas PGRI Madiun, 2026)
Early childhood children generally spend more time playing than studying. This will certainly impact children's learning activities. The purpose of this study is to describe the role of parents in accompanying early childhood learning activities. This type of research is field research using a descriptive qualitative approach. Data in this study were obtained through observation, interviews, and documentation. In analyzing the data, the researcher used three stages: reduction, data presentation, and conclusion. Based on the results of this study, parents play a very important role in supporting early childhood learning activities, including instilling habits in everyday life, such as teaching children to respect others. Furthermore, supporting and inhibiting factors for parents when accompanying children include: implementing the learning provided by teachers at school, and parents' lack of patience when accompanying children in learning activities at home.